Crack propagation in high modulus asphalt mixtures - Sewell, Anthony J. (2017)
This Thesis was undertaken at the University of Nottingham which has a world class history of research into the fatigue of asphalt materials. The work described in this thesis was part of a research project funded by EPSRC, which attempts to gain a greater understanding of fatigue crack propagation in High Modulus Base (HMB) materials. Following on from Pell, Brown and Read this research has introduced the Compact Tension (CT) Test and Fracture Mechanics principles to examine the behaviour of HMB materials which had relatively little fatigue behavioural understanding on commencement of this research. This research investigated the fatigue cracking behaviour of twelve High Modulus Base (HMB) binders and mixtures. The research was instigated in response to the introduction of these HMB binders from France, as it was thought that these materials were not particularly well understood. In hindsight, this view was proven to be correct, as numerous problems have been experienced after using such materials. The Compact Tension test has been proved to be an effective means of testing bituminous mixtures for their crack propagation resistance, allowing the study of temperature effects. Crack propagation is dramatically affected by both binder hardness and temperature. In a pavement, the current approach to design, assuming a single fatigue characteristic, underestimates the life of 35 and 25 pen mixtures. However, it probably overestimates the life of 15 pen mixtures by not accounting for the effects of low temperatures.